2022
DOI: 10.1021/acs.est.1c03780
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Zwitterionic PFAS by MXenes: Comparisons with Anionic, Nonionic, and PFAS-Specific Resins

Abstract: Zwitterionic per- and polyfluoroalkyl substances are increasingly detected in aquatic environments. The magnitude of their concentration and increased frequency of detection worldwide raise questions on their presence in drinking water and associated health risk. Scientific knowledge on the identification of treatment technologies to effectively capture such zwitterionic PFAS from contaminated water sources remains largely unknown. In this study, we investigated the application of anionic organic scavenger ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 78 publications
0
10
0
Order By: Relevance
“…PFASs generally resist degradation, posing considerable challenges to established water treatment and waste disposal practices. The removal and degradation of PFASs from water can be achieved by various approaches, such as photocatalytic degradation, reductive defluorination, enhanced adsorption, electrochemical approaches, supercritical water oxidation, plasma , and nonthermal plasma, , and hydrothermal methods assisted with base and aprotic solvents . However, much fewer options are available to handle solid materials containing PFASs. , In this study, we have demonstrated that the innovative approach of induction heating can significantly degrade PFASs in spent media within a short period.…”
Section: Discussionmentioning
confidence: 84%
“…PFASs generally resist degradation, posing considerable challenges to established water treatment and waste disposal practices. The removal and degradation of PFASs from water can be achieved by various approaches, such as photocatalytic degradation, reductive defluorination, enhanced adsorption, electrochemical approaches, supercritical water oxidation, plasma , and nonthermal plasma, , and hydrothermal methods assisted with base and aprotic solvents . However, much fewer options are available to handle solid materials containing PFASs. , In this study, we have demonstrated that the innovative approach of induction heating can significantly degrade PFASs in spent media within a short period.…”
Section: Discussionmentioning
confidence: 84%
“…Similarly, high-performance or ultra-high-performance liquid chromatography (HPLC or UHPLC) was also employed by many researchers, as shown in Table 3. In terms of mass spectrometry, the most commonly reported spectrometers for PFAS also included triple quadrupole (QqQ), quadrupole time-of-flight (QTOF), and quadrupole-orbitrap in positive or negative electrospray ionization (ESI) modes [86][87][88][89]. Typically for atmospheric or dust samples, gas chromatography mass spectrometry (GCMS) equipped with electron impact (EI) [38], electron capture negative ion (ECNI) [90], and mass selector detector (MSD) [91] have been used by researchers.…”
Section: Analytical Methods For the Detection And Quantification Of Pfasmentioning
confidence: 99%
“…This new family of 2D materials known as MXenes are derived from selective etching of their precursor MAX phase, realizing unique characteristics as a result of quantum confined electrons [11]. Despite being in their infancy, MXenes have gained explosive attention among researchers of almost all genres, namely microelectronics [12], tribology [13], battery electrodes [14], conductive inks [15], biomedicine [16,17] and solar thermal desalination [18,19]. Often regarded as 'wonder materials' MXenes are flexible, miniaturized, optically transparent layered structures with the chemical formula M n+1 X n T 2 where M denotes early transition metals, X is a carbon and/or nitrogen, and T is a surface termination functional group [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%